1991
DOI: 10.1016/0042-6822(91)90071-i
|View full text |Cite
|
Sign up to set email alerts
|

The complete sequence (22 kilobases) of murine coronavirus gene 1 encoding the putative proteases and RNA polymerase

Abstract: The 5'-most gene, gene 1, of the genome of murine coronavirus, mouse hepatitis virus (MHV), is presumed to encode the viral RNA-dependent RNA polymerase. We have determined the complete sequence of this gene of the JHM strain by cDNA cloning and sequencing. The total length of this gene is 21,798 nucleotides long, which includes two overlapping, large open reading frames. The first open reading frame, ORF 1a, is 4488 amino acids long. The second open reading frame, ORF 1b, overlaps ORF 1a for 75 nucleotides, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
459
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(469 citation statements)
references
References 51 publications
10
459
0
Order By: Relevance
“…One of the initial steps in MHV replication is the translation of gene 1 from the input genomic RNA. Gene 1 encompasses approximately 21.8 kb at the 5' end of the genome and contains two overlapping large open reading frames (Lee et al, 1989;Bonilla et al, 1994). The ®rst open reading frame ORF1a encodes 4469 amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…One of the initial steps in MHV replication is the translation of gene 1 from the input genomic RNA. Gene 1 encompasses approximately 21.8 kb at the 5' end of the genome and contains two overlapping large open reading frames (Lee et al, 1989;Bonilla et al, 1994). The ®rst open reading frame ORF1a encodes 4469 amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…The murine coronavirus (mouse hepatitis virus, MHV) genome of 31 kb (Spaan et al, 1988;Lee et al, 1991) encodes four major structural proteins and several nonstructural proteins. The structural proteins are the nucleocapsid (N) protein of about 50K, the membrane (M) protein of 20K to 25K, the haemaggglutininesterase (HE) protein of about 65K and the spike (S) protein of 150K to 180K (Siddell et al, 1983;Spaan et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…A novel coronavirus, named SARS coronavirus (SARS-CoV), was soon identified as the etiological agent of the infection (1)(2)(3). It was revealed that the open reading frame of the replicase gene in SARS-CoV genome, similar to other coronaviruses (4,5), features the sequence motifs of both papainlike proteinase and 3C-like proteinase (3CL pro ). SARS 3CL pro is fully conserved among all released SARS coronavirus genome sequences and is highly homologous to other coronavirus 3CL proteinases (6,7).…”
mentioning
confidence: 99%